القوامة الزوجية عند مسلمي بانكوك: مفهومها ومشاكلها وحلولها في ضوء الفقه الإسلامي = Marital guardianship (Qiwāmah) among the Muslims of Bangkok: concept‚ problems and solutions in light of Islamic law - Nawawee, Arawan; Mahmud, Mek Wok (IIUM Press, International Islamic University Malaysia, 2020)
This research aims to study the topic of marital guardianship (qiwāmah) as practiced by Muslims of Bangkok, Thailand, who wrongly understand that the qiwāmah means to have absolute control over their women. This research focuses on providing solutions for this problem for the Muslims in Bangkok. The researchers have adopted the inductive and analytical methods, as well as a field study consisting of questionnaires, interviews, visits to common Muslims, judges, imams of mosques and members of the Islamic Committee in Bangkok. The research is divided into two sections: first, the study of qiwāmah, its concepts and implications in the Islamic law; and second, the problems faced by Muslims of Bangkok due to their wrong understanding of the concepts and how to solve them from the perspective of the Islamic law and a field study. The research concludes that Muslims of Bangkok are a minority ruled by Buddhist authorities of Thailand. As a result, they are largely ignorant about the rules of family in Islam and the sound understanding of qiwāmah.